Enlarging the π-conjugation of cobalt porphyrin for highly active and selective CO₂ electroreduction - Dou, Shuo (2022)
Heterogeneous molecular catalysts have attracted considerable attention as carbon dioxide reduction reaction (CO2 RR) electrocatalysts. The π-electron system of conjugated ligands in molecular catalysts may play an important role in determining the activity. In this work, by enlarging π-conjugation through appending more aromatic substituents on the porphyrin ligand, altered π-electron system endows the as-prepared 5,10,15,20-tetrakis(4-(pyren-1-yl)phenyl)porphyrin CoII with high Faradaic efficiency (ca. 95 %) for CO production, as well as high turnover frequency (2.1 s-1 at -0.6 V vs. RHE). Density functional theory calculation further suggests that the improved electrocatalytic performance mainly originates from the higher proportion of Co dz2 orbital and the CO2 π* orbital in the HOMO of the (Co-porphyrin-CO2 )- intermediate with larger π-conjugation, which facilitates the CO2 activation. This work provides strong evidence that π-conjugation perturbation is effective in boosting the CO2 RR.